MULTIPLE SCHMORL’S NODES ON YOUNG ADULT WITH MYOFASCIAL PAIN SYNDROME: A CASE REPORT - I Gusti Agung Ayu Andra Yusari; Putu Gede Sudira; Ida Ayu Sri Wijayanti (Malang Neurology Journal, 2023)
Background: Schmorl’s node (SN) is described as intraosseous disc herniations which penetrate into the spinal canal, which is caused by the weakening of the cartilaginous endplate and subchondral bone. SN is usually detected on imaging which appears small, focal, and rounded with varying degrees of adjacent reactive sclerosis.